2017
DOI: 10.1111/jace.14975
|View full text |Cite
|
Sign up to set email alerts
|

Development of brannerite glass‐ceramics for the immobilization of actinide‐rich radioactive wastes

Abstract: Brannerite‐based glass‐ceramics have been developed as potential waste forms for the immobilization of actinide‐rich radioactive wastes. For the first time, the formation of brannerite phases in glass has been demonstrated using uranium (U) and plutonium (Pu) with additions of gadolinium and hafnium as neutron absorbers. Both XRD and SEM‐EDS confirm that brannerite is the dominating phase with compositions close to Y0.5U0.5Ti2O6, Gd0.2Pu0.3U0.5Ti2O6, and Gd0.1Hf0.1Pu0.2U0.6Ti2O6 internally crystallized in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 50 publications
(153 reference statements)
2
31
0
Order By: Relevance
“…It has been suggested that the presence of U 5+ /U 6+ in titanate phases has no significant effect on their chemical durabilities because their dissolutions are not only controlled by U valences but also by the low solubility of the titanate materials. In addition, the short‐term static leaching tests also confirmed that the brannerite GCs are chemically durable and potential waste forms for actinide‐rich radioactive wastes . Above all, the glass matrix also provides the secondary barrier for GC waste forms to prevent and control the actinide releases from the host ceramic phases.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…It has been suggested that the presence of U 5+ /U 6+ in titanate phases has no significant effect on their chemical durabilities because their dissolutions are not only controlled by U valences but also by the low solubility of the titanate materials. In addition, the short‐term static leaching tests also confirmed that the brannerite GCs are chemically durable and potential waste forms for actinide‐rich radioactive wastes . Above all, the glass matrix also provides the secondary barrier for GC waste forms to prevent and control the actinide releases from the host ceramic phases.…”
Section: Resultsmentioning
confidence: 66%
“…All 3 GC samples were fabricated (including precursor calcination and heat treatment for the final products) under air atmosphere as earlier work has demonstrated that the low oxygen fugacity in the melting glass is sufficient to stabilize pentavalent uranium titanate phases with the additional chemical control (the addition of di‐/trivalent cations) . Note hexavalent uranium in uranyl nitrate [(UO 2 )(NO 3 ) 2 ] form was the starting material for the brannerite precursors targeting the crystallization of the 3 brannerite phases in glass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the presence of Ln 3+ ions in the designed brannerite phases, the U 5+ ion is expected to maintain the charge balance based on the EDS analysis results. The optical absorption of the U 5+ ion is confined to the near infrared as it derives only from the crystal field splitting of 2 F 5/2 − 2 F 7/2 components (split by spin‐orbit coupling) of the 2 F electronic state, with major strong electronic transitions observable from the splitting of 2 F 7/2 at 1538‐833 nm (6500‐12 000 cm −1 ) The DRS of samples U1B, U2B, U3A, and U4A (Figure ) in the 800‐2500 nm (12500‐4000 cm −1 ) region clearly show the presence of the U 5+ ion as anticipated, with the sharp and strong bands at 1444 nm (6925 cm −1 ) for U1B and U3A, and 1445 nm (6920 cm −1 ) for U2B and U4A, corresponding to the typical f – f transition in a 5 f 1 configuration, consistent with the earlier observations of U 5+ ion stabilized in brannerite . Other weak to medium absorption bands in the near infrared region are broadly consistent with the U 5+ free ion energy levels .…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] This implies that both brannerite and brannerite-based glass-ceramics may have potential as waste forms for spent nuclear fuels and some U-rich radioactive wastes such as the intermediate-level radioactive wastes generated from the production of 99 Mo for nuclear medicines. Given that plutonium ions can be stabilized in brannerite, 38 brannerite glass-ceramics may also have the potential as waste forms for plutonium residue wastes with processing chemicals. Such anticipation will be the motivation to explore the formation and crystal chemistry of brannerite phases with Pu 3+ /Pu 4+ ions in future studies.…”
Section: Discussionmentioning
confidence: 99%